EFEKTIVITAS MODEL PEMBELAJARAN PROJECT ACTIVITY COOPERATIVE EXERCISE (PACE) TERHADAP MINAT BELAJAR PAI DAN BUDI PEKERTI - Munawaroh, Puji; Ruswanto; Susilawati, Beti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the problem of low student interest in learning Islamic Religious Education and Character Building, especially in the aspect of learning interest because learning is still dominated by conventional methods, monotonous learning models and the use of less varied learning media. A learning model is needed that can help students more easily understand the material and encourage cooperation between each other. One way that can be done to overcome obstacles in the learning process and increase student interest in learning is by implementing the right learning approach. A comprehensive and integrated approach is key in efforts to improve the quality of learning. One learning model that can be applied is PACE (Project Activity Cooperative Exercise). The study used a quantitative approach with a Quasi-Experimental Design type. The sample amounted to 60 students selected through a simple random sampling technique. Data were collected using a Likert scale questionnaire to measure Learning Interest, then analyzed with a regression test. The results of the study showed that the Project Activity Cooperative Exercise (PACE) learning model was able to increase student interest in learning through active involvement in projects, activities, cooperation, and exercises. This model is considered relevant because it not only emphasizes conceptual understanding but also fosters students' enjoyment, attention, and interest in Islamic Religious Education (PAI) and Character Education (Culture).